Pemahaman Masyarakat di Nagari Suayan Mengenai Batasan Pergaulan Antar Lawan Jenis (Studi Living Qur’an) - Fitri, Rindiani; Febriyeni, Febriyeni (Darul Yasin Al Sys, 2023)
The author's background in conducting this research is the fact that relationships occur in a society that has experienced decline, therefore the formulation of the problem of this research is how society understands the limits of relationships between the opposite sex, and how the regulations made by the government are aligned, niniak mamak, and religious scholars who aim to revive a generation that understands the rules regarding social relations, here the government in Nagari Suayan has tightened the existing regulations in Nagari Suayan as well as its customary regulations. Apart from reviving a society that obeys the rules, it also forms a generation that is in accordance with the Koran. This research uses the living Qur'an method, the data information of which is obtained from interviews with several respondents who are residents of Nagari Suayan, observation and documentation. This research presents data in qualitative form in several ways, namely by data reduction, data presentation and drawing conclusions. People's understanding of the limits of interaction between the opposite sex in the Koran. People in Nagari Suayan generally already know how to socialize in accordance with what the Koran teaches, this can be seen from their answers when interviewed. The regulations made by the government in Nagari Suayan, initiated by Niniak Mamak, a religious scholar in Nagari Suayan, aim to maintain the security and welfare of the community, while sanctions for violating the law do not only apply to the government but also apply to customs. If in the government the sanction is in the form of a fine as much as has been determined, then in custom there is also a fine in the form of one buffalo, and it is not permissible to hold wedding parties for those found committing adultery and being pregnant out of wedlock. Alignment of government regulations, niniak mamak, and religious scholars in Nagari Suayan regarding the limits of interaction between members of the opposite sex in accordance with the Qur'an.